INFLUENCE OF COUNSELLING SERVICES ON NON TEACHING STAFF PERFORMANCE IN PUBLIC UNIVERSITIES OF NAKURU COUNTY, KENYA (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
Employees are the most important human resource an organization cannot do without. They make a significant contribution to the success of an organization. Currently there is increased pressure for employees to be productive at their work place. This pressure is presented by the need to deliver the expected product or service in the market place while fulfilling the organizations mission and vision. Most employees suffer from a number of personal issues such as emotional, family and home life conflicts, mental health concerns, substance abuse problems, and other health disorders that if not attended to has the capability of negatively influencing on their effective performance. The purpose of the study was to assess the influence of counselling services on non teaching staff performance. The study was guided by person centred theory. The target population comprised administrative staff. Purposive sampling was used to select the administrators in public universities of Nakuru county. Census was used to get a sample size of 91 respondents. A structured questionnaire was administered to provide the required data. The questionnaire was pilot tested to ascertain its validity and reliability. Reliability coefficient of 0.733 was found and considered reliable. The study employed both descriptive and inferential statistics to present and analyze the data Statistical Package for Social Science (SPSS) version 22 a computer program for windows aided in data analysis. The findings of the study revealed that there that there was a moderate statistically significant positive relationship of (r = 0.472, p < 0.05) between Counselling services and Employee performance. Recommendations were that HR departments in public Universities needs to sensitize employees on the provision of counselling services. These services should also be designed to address employee needs and frequently offered as the need arises. . The study also recommends that further research could be carried out in other cadre of profession in both public and private universities to establish the differences.